Exploring Trends in Physics Practicum: A Literature Review and Bibliometric Analysis - Herman, Herman; Kaniawati, Ida; Setiawan, Agus; Rusdiana, Dadi (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to conduct a literature review on physics practicum using the Systematic Literature Review (SLR) method and bibliometric analysis through visual mapping with the VOSviewer software. The focus of this research is on articles published between 2020 and 2025, with the keyword "Physics Practicum." A total of 122 articles were identified, with 14 selected for the literature review. The results indicate that the number of publications on physics practicum decreased from 2020 to 2023, increased in 2024, and then declined again in 2025. The study also reveals that both conventional and digital technologies, such as Arduino-based sensors, smartphone applications, wireless sensor networks, as well as advanced technologies like Augmented Reality (AR), Virtual Reality (VR), and e-learning platforms, have enhanced the effectiveness of physics practicum. However, significant research gaps remain, particularly in the development of worksheets and assessment tools that provide a holistic evaluation of psychomotor skills and overall practicum performance. The bibliometric analysis using VOSviewer highlights keyword mapping that clusters aspects of methodology, evaluation, technology, and external factors such as the pandemic, offering valuable insights for future development of physics practicum.